(untitled) (SAARC Journal of Agriculture, 2018)
The nutrient profile of five carps, viz. Labeo bata, Labeo calbasu, Labeo fimbriatus, Cirrhinus reba and Puntius javanicus were studied. The samples were collected from different geographical locations of West Bengal, Odisha and Karnataka states of India. The data on proximate composition reveal that the moisture and fat content differed significantly (P<0.01) among the carp species. The fat content is significantly (P<0.01) higher in P. javanicus, L. bata and L. calbasu compared to L. fimbriatus. However, the protein and ash content did not differ significantly among the carp species. The potassium and copper contents differed significantly (P<0.01) among the fish species. Both potassium and copper contents were significantly higher in L. bata. The calcium content was maximum in L. fimbriatus. The saturated fatty acid (SFA), mono unsaturated fatty acid (MUFA) and poly unsaturated fatty acid (PUFA) differed significantly (P<0.01) among all the carp species. The palmitic acid was significantly higher in L. fimbriatus, which is the predominant SFA. Among MUFA, the oleic acid was significantly higher in P. javanicus. The total MUFA was significantly (P<0.05) higher in C. reba. eicosapentaenoic acid (EPA) and total PUFA is significantly higher in L. bata. Among the essential amino acids, methionine was maximum in L. fimbriatus, P. javanicus and L. bata whereas in case of nonessential amino acids, the glutamic acid and aspartic acid were high in C. reba and L. calbasu. The gross energy content of the fish was higher in L. fimbriatus followed by C. reba and L. bata. The nutrient profile of these fish species reveal that they were rich in essential nutrients required for human health SAARC J. Agri., 16(1): 215-231 (2018)